Antibiotic resistance determinants and clonal relationships among multidrug-resistant isolates of Klebsiella pneumoniae. (September 2017) - Singh, Santosh Kumar; Mishra, Mitali; Sahoo, Minu; Patole, Shashank; Sahu, Suneeta; Misra, Sudhi Ranjan; Mohapatra, Harapriya
Abstract: In the present study, we performed PCR based screening to determine the presence of antibiotic resistance genes and sequencing to find mutation in QRDR region among fourteen isolates of K. pneumoniae . Association analysis was conducted to detect the co-resistance among the isolates. Multi-locus sequence analysis was carried out to determine the clonal relationship among them. All the K. pneumoniae isolates showed resistance to multiple antibiotics and exhibited cross-resistance to antibiotics. Although few isolates co-harbored variants of β-lactamase genes, others carried qnrB on plasmid and mutations in Quinolone-Resistant Determining Region (QRDR). This study thus indicates that clonally unrelated K. pneumoniae isolates exhibited co-resistance, harboured multiple antibiotic resistance genes present on the chromosome, plasmids and/or integron Therefore, the data from this study can provide guidelines for the prudent use of antibiotics to avert the impending danger of losing out on the available antibiotics for therapeutic use. Highlights: Clinical isolates of Klebsiella pneumoniae were multidrug resistance and co-harbored variants of β-lactamase genes. Four isolates have both plasmid mediated quinolone resistant gene ( qnrB ) and mutation in QRDR of gyrA gene. Resistance genes were encoded on chromosome, plasmids and integron. Six MDR Klebsiella pneumoniae isolates belongs to ST14, ST231, ST307, ST327, ST721 and ST1310.